Analysis of Family Nutrition and Physical Activity (FNPA) and food security as predictors of adolescent obesity at SMAN 98 Jakarta - Annisa Yuri Ekaningrum; Hilda Carmitha Panjaitan; Dany Permana (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Obese adolescents are at an increased risk of obesity in adulthood. The Family Nutrition and Physical Activity (FNPA) screening tool was developed for children and adolescents to identify families at risk and facilitate early obesity counseling and intervention strategies. This study aimed to examine the association between family nutrition and physical activity (FNPA), household food security, and nutritional status among adolescents. A cross-sectional study was conducted at SMAN 98 Jakarta, involving 318 students in June and July 2026. Nutritional status was assessed using BMI-for-age, FNPA was measured using a standardized questionnaire, and food security was assessed using the Household Food Insecurity Access Scale. Data were analyzed using chi-square tests, correlation analysis, and multinomial logistic regression analysis. The results showed No significant association was found between food security and nutritional status (p = 0.448). FNPA scores were not significantly correlated with BMI-for-age Z-scores (r = 0.018; p = 0.751). Multinomial logistic regression analysis showed that sex was the only variable significantly associated with nutritional status, with female adolescents more likely to have a normal nutritional status than undernutrition (p = 0.036; OR = 2.934; 95% CI: 1.073–8.022). In conclusion, these findings suggest that family environment and household food security alone may not sufficiently explain adolescent obesity, highlighting the role of broader behavioral and environmental factors in adolescent obesity.